A novel fabrication method for a TiO2 layer over CoCr alloy. (4th March 2019) - Cetiner, Dogukan; Paksoy, Ahmet Hilmi; Tazegul, Onur; Baydogan, Murat; Guleryuz, Hasan; Cimenoglu, Huseyin; Atar, Erdem
ABSTRACT: This study has been initiated to form a TiO2 layer having enhanced biological properties on the surface of a CoCr alloy, which is mostly used in manufacturing of orthopaedic implants. As a novel approach, CoCr alloy samples were first coated with titanium and then oxidised in air at 600°C for 60 h. Surface characterisation of the samples were made by structural surveys (scanning electron microscopic examinations, X-ray diffraction analyses), roughness and hardness measurements, bioactivity and wear tests. Results of the experiments have showed that fabrication of TiO2 as the outermost surface layer caused remarkable increment in the wear resistance and the bioactivity of the CoCr alloy.